PERAN SEKTOR INFORMAL TERHADAP PENYERAPAN TENAGA KERJA (Studi Pada Pedagang Pasar Tugu Kota Malang) - Hapsari, Lathifa (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
In facing complicated problems of poverty and unemployment due to lack of employment opportunities in formal sector, informal sector comes up its important role within the plan and structure of city employment. Informal sector which tends flexible and less-barrier preferred by employment force that unable to penetrate into modern industry sector. This study aims to understand the characteristic of informal sector enterprises, also to analyze its role of employment which focused to the internal factors of enterprises including wages, productivity, and capital in Pasar Tugu Malang City. This study uses quantitative descriptive approach with Ordinary Least-Square as analysis method. The sampling technique used is random sampling with 60 merchants of Pasar Tugu as respondents. The result applied to each of independents variables shows that particularly, variable wages (X1) has significant effect towards employment (Y), meanwhile variables productivity (X2) and capital (X3) don’t have significant effect towards employment (Y). As results of F-test, shown that simultaneously variables wages (X1), productivity (X2), and capital (X3) have significant effect towards employment (Y) in accordance to value of Fstat > Ftable (10,787 > 2,90) and significant value < α (0,000 < 0,05).Keywords : Informal sector, employment, wages, productivity, capital.